Fundamental Social Motives Measured Across Forty-Two Cultures in Two Waves - Fernandez-Tapia, A (Nature Research, 2022)
H﻿ow does psychology vary across human societies? The fundamental social motives framework adopts an evolutionary approach to capture the broad range of human social goals within a taxonomy of ancestrally recurring threats and opportunities. These motives—self-protection, disease avoidance, affiliation, status, mate acquisition, mate retention, and kin care—are high in fitness relevance and everyday salience, yet understudied cross-culturally. Here, we gathered data on these motives in 42 countries (N = 15,915) in two cross-sectional waves, including 19 countries (N = 10,907) for which data were gathered in both waves. Wave 1 was collected from mid-2016 through late 2019 (32 countries, N = 8,998; 3,302 male, 5,585 female; Mage = 24.43, SD = 7.91). Wave 2 was collected from April through November 2020, during the COVID-19 pandemic (29 countries, N = 6,917; 2,249 male, 4,218 female; Mage = 28.59, SD = 11.31). These data can be used to assess differences and similarities in people’s fundamental social motives both across and within cultures, at different time points, and in relation to other commonly studied cultural indicators and outcomes. © 2022, The Author(s).